Adaptive full-diversity full-rate space-time block code with linear decoding complexity - Wang, Li; Jiang, Hua; Shao, Lan; Zhao, Hui; Wang, Wenbo (Proceedings, 2009 3rd IEEE International Symposium on Microwave, Antenna, Propagation and EMC Technologies for Wireless Communications : 27-29 October 2009, Beijing, China, 2009)
We propose an adaptive space-time block code (A-STBC) for the wireless communication system. A group of minimum-decoding-complexity quasi-orthogonal STBC (MDC-QO-STBC) matrices which are the same size and code rate but different in the performance of combating inter-symbol-interference are obtained, and a specific matrix is selected from the group for a certain channel according to its channel state information. For the proposed A-STBC, linear decoding can be used in a system with four transmit antennas, thus the lowest decoding complexity is achieved, in addition, full-diversity and full-rate can also be obtained. The simulation results show that the A-STBC has a lower block error ratio (than normal MDC-QO-STBC) and a higher throughput (than single-user precoding). A-STBC is an effective combination of the simplification in decoding and the performance advantages in block error rate as well as throughput.